Management building competitive advantage - Bateman Thomas S.; Snell Scott A. (Irwin, 1996)
Focusing on management and building competitive advantage, this text is organized around the themes of cost, quality, speed and innovation. It includes business examples and management research, as well as coverage of NAFTA, European unification, strategic alliances and the MBA Enterprise Corps.